ANALYSIS OF THEMATIC GROUPS IN CLOTHING NAMES IN UZBEK AND ENGLISH LANGUAGES - Normurodova Farogat Tojimurod kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. The present article is devoted to the comparative analysis of clothing names in the Uzbek and English languages from a thematic and linguocultural perspective. Clothing terminology represents an important lexical-semantic field that reflects material culture, national traditions, social structure, and historical development of a society. The study aims to identify major thematic groups of clothing names, to compare their semantic and structural features, and to reveal their linguocultural specificity. The research is based on descriptive, comparative, and semantic analysis methods. The findings show that although Uzbek and English clothing names share common thematic categories, they differ significantly in cultural motivation, lexical structure, and symbolic meaning. The results of the study may be useful for comparative lexicology, linguoculturology, translation studies, and language teaching.